Inhibition of Contractile Function in Human Joint Capsule Myofibroblasts by Targeting the TGF-β1 and PDGF Pathways. - Stefan G Mattyasovszky (PLoS ONE, 2016)
Contractile myofibroblasts (MFs) accumulate in the joint capsules of patients suffering from posttraumatic joint stiffness. MF activation is controlled by a complex local network of growth factors and cytokines, ending in the increased production of extracellular matrix components followed by soft tissue contracture. Despite the tremendous growth of knowledge in this field, inconsistencies remain in practice and prevention.In this in vitro study, we isolated and cultured alpha-smooth muscle actin (α-SMA) positive human joint capsule MFs from biopsy specimens and investigated the effect of profibrotic and antifibrotic agents on MF function. Both TGF-β1 and PDGF significantly induced proliferation and increased extracellular matrix contraction in an established 3D collagen gel contraction model. Furthermore, both growth factors induced α-SMA and collagen type I gene expression in MFs. TGF-β1 down-regulated TGF-β1 and TGF-β receptor (R) 1 and receptor (R) 2 gene expression, while PDGF selectively down-regulated TGF-β receptor 2 gene expression. These effects were blocked by suramin. Interestingly, the anti-oxidant agent superoxide dismutase (SOD) blocked TGF-β1 induced proliferation and collagen gel contraction without modulating the gene expression of α-SMA, collagen type I, TGF-β1, TGF-β R1 and TGF-β R2.Our results provide evidence that targeting the TGF-β1 and PDGF pathways in human joint capsule MFs affects their contractile function. TGF-β1 may modulate MF function in the joint capsule not only via the receptor signalling pathway but also by regulating the production of profibrotic reactive oxygen species (ROS). In particular, anti-oxidant agents could offer promising options in developing strategies for the prevention and treatment of posttraumatic joint stiffness in humans.